2010
DOI: 10.1002/ajmg.a.33417
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cranial nerve neuropathies, microcephaly, neurological degeneration, and “fork and bracket sign” in the MRI: A distinct syndrome

Abstract: We report on two sibs with an elongated face with reduced expression, microcephaly, strabismus, wide philtrum, mild joint laxity, thumb sign, bilateral foot drop, and fixed pes cavus, absent tendinous reflexes, an unsteady gait, quick fatigue, slightly diminished limb muscle strength more pronounced distally, abnormalities of cranial nerves III, IV, VII, and most probably VI, and slowness in ideation. Previously unknown findings referred to as the "fork sign" at the pontine level and the "bracket sign" at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…Axial slice through the mesencephalon showed bright signal from the oculomotor nuclear complex, and related degenerated internal fibers of the oculomotor nerves (Figure B). These highly unique “fork and bracket” MRI signs were previously described only once, in one of the SBF1 ‐mutated families . Our findings represent the second case described to date, delineating this MRI finding as a unique diagnostic sign.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Axial slice through the mesencephalon showed bright signal from the oculomotor nuclear complex, and related degenerated internal fibers of the oculomotor nerves (Figure B). These highly unique “fork and bracket” MRI signs were previously described only once, in one of the SBF1 ‐mutated families . Our findings represent the second case described to date, delineating this MRI finding as a unique diagnostic sign.…”
Section: Resultssupporting
confidence: 73%
“…These highly unique "fork and bracket" MRI signs were previously described only once, in one of the SBF1-mutated families. 8 Our findings represent the second case described to date, delineating this MRI finding as a unique diagnostic sign.…”
Section: Clinical Characterizationsupporting
confidence: 60%
See 1 more Smart Citation
“…34 . Rare and novel autosomal recessive disorders have been widely reported from communities with high consanguinity rates [35][36][37][38][39][40][41][42] , since the main impact of consanguinity is the increased expression of rare autosomal recessive genetic disorders.…”
Section: Health Impact Of Consanguinitymentioning
confidence: 99%
“…The phenotype of the first family is consistent with CMT4B with a demyelinating progressive sensory-motor neuropathy with myelin outfoldings without associated features; the 3 affected sisters were compound heterozygotes for two missense mutations, p.M417V and p.T1590A, 36 both predicted as benign or tolerated by in-silico analyses and therefore with a mild impact on the protein. Conversely, the Syrian family had an axonal motor neuropathy with microcephaly, intellectual disability, multiple cranial neuropathies, and "the fork and the bracket" signs on brain MRI showing the abnormal cranial nerves 52 ; the 2 affected siblings carried a homozygous mutation, p.L335P, located next to the critical dDENN domain and predicted to be highly deleterious for protein function. 34 The fork and bracket signs, first described by Megarbane et al 52 and later by Flusser et al in another CMT4B3 family, 32 have not been reported in other conditions thus far.…”
Section: Cmt4b3mentioning
confidence: 99%